Asuhan Keperawatan Jiwa Pada Ny. T Dengan Masalah Utama Risiko Perilaku Kekerasan Akibat Skizofrenia Paranoid di Ruang Dewaruci RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Cici Afriani; Titi Sri Suyanti; Tati Karyawati (Jurnal Anestesi, 2024)
Schizophrenia is a serious mental disorder with clinical manifestations such as: delusions (false beliefs), hallucinations, loss of contact wit reality (psychoisis), risk of violent behavior, abnormal thoughts that can inhibit daily activities that give rise to emotions, perceptions, thoughts, movement and behavior (Pertiwi et al., 2023). The purpose of this paper is to determine and provide psychiatric nursing care to Mrs. T with the main problem of the risk of violent behavior due to paranoid schizophrenia in the Dewaruci ward of dr. Amino Gondohutomo Mental Hospital, Cental Java Province in accordance with nursing standards. The method used is a descriptive method in the form of interviews, observations, documentation studies and literature studies. From the case review, it was found that the patients main complaint said “I was angry, shouted and even punched the door twice, ma’am”. There are 3 nursing problems, namely the risk of violent behavior, self-care deficit. Interventions are arranged base on TUM and TUK as well as on the client’s condition and can be implemented.